The Evolutionary Roots of Familial Altruism: Paternity Uncertainty Shapes Patterns of Kindness - Kuba, Radim; Flegr, Jaroslav (Evolutionary psychology, 2025)
We investigated how paternity uncertainty (PU) shapes perceptions of familial kindness. We predicted that relatives with lower PU would be rated as kinder than those with higher PU. A total of 9,128 participants rated the kindness of specific relatives in their families. Main analyses focused on parents and maternal/paternal grandparents, who differ in their typical levels of PU. Siblings were included for broader within-family comparisons, while step-relatives, all having identical (maximal) PU, served as negative controls. Controlling for sex, age, and random effects of raters and targets, results supported PU predictions: PU showed a negative correlation with rated kindness (β = -0.148, t(31,910) = -6.23, p < 0.001, with the full model (including PU) significantly outperforming a reduced model (χ²(2) = 42.84, p < 0.001). Post-hoc tests revealed significant differences between adjacent PU levels (0 vs. 1: p < 0.001, d = 0.15; 1 vs. 2: p = 0.0002, d = 0.08). Mothers and maternal grandmothers (no PU) were rated the kindest, while the paternal grandfather (two PU) was rated lowest. Daughters consistently rated their biological parents higher than sons, possibly reflecting lower PU through female offspring. Maternal grandfathers were rated kinder than fathers, despite identical PU, perhaps due to redirected investment by non-reproducing elders. Furthermore, mothers were rated kinder than maternal grandmothers, possibly due to "insider knowledge" of their children's paternity. Step-relatives showed minimal variation, suggesting that observed differences among biological kin reflect genetic relatedness and PU, rather than non-genetic factors. Overall, our findings support kin selection theory and suggest that paternity uncertainty subtly yet systematically shapes perceptions of familial kindness.
Keywords: prarodiče; paternita; rodina; Humans; altruism; lidé středního věku; dítě; Family; Child; grandmothers; Female; rodiče; mladý dospělý; dospělí; Biological Evolution; kindness; stepfamily; lidé; kin selection theory; Parents; nejistota; Grandparents; Adult; ženské pohlaví; paternity certainty‌; Male; Middle Aged; Uncertainty; biologická evoluce; Adolescent; Paternity; Young Adult; Altruism; mužské pohlaví; altruismus; mladiství